Efficacy and toxicity of carfilzomib- or bortezomib-based regimens for treatment of transplant-ineligible patients with newly diagnosed multiple myeloma: A meta-analysis. Issue 39 (30th September 2022) - Xie, Chunhong; Wei, Min; Yang, Feiyan; Liu, Qin; Wu, Fuzhen; Huang, Jinxiong
Abstract : Background: Multiple myeloma is a clonal disorder of malignant plasma cells that comprises approximately 10% of hematologic malignancies. The aim of this study was to investigate the efficacy and toxicity of carfilzomib- or bortezomib-based regimens for treatment of transplant-ineligible patients with newly diagnosed multiple myeloma by performing a meta-analysis of randomized controlled trials (RCTs). Methods: Data mining was conducted in March 2022 across PubMed, EMBASE and ClinicalTrials.gov . All published RCTs which assessed efficacy and toxicity of carfilzomib-based regimens treatment for transplant-ineligible patients with newly diagnosed multiple myeloma when compared with a bortezomib-based regimens were included. Results: Our meta-analysis showed that the overall response rate (ORR) (Odds ratio = 1.33, 95% CI 1.05–1.69, P  = .02) was significantly higher in the carfilzomib-based regimens group than in the bortezomib-based regimens group. However, the difference in ORR did not translate into improvements in progression-free survival (PFS), overall survival (OS) and complete response rate (CRR). Adverse events of grade 3 or worse that occurred with a higher incidence in the carfilzomib-based regimens group compared with the bortezomib-based regimens group were dyspnea, hypertension, acute kidney injury, and heart failure. Conclusions: The carfilzomib-based regimens did not improve PFS, OS and CRR compared with the bortezomib-based regimens in transplant-ineligible patients with newly diagnosed multiple myeloma, and they showed higher toxicity.